SUPLEMENTASI SUMBER ENERGI DAN PROTEIN BERBEDA DEGRADASI PADA PAKAN BASAL TUMPI JAGUNG DAN KULIT KOPI TERHADAP KINERJA SAPI POTONG - , DICKY PAMUNGKAS ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The use of agricultural by product as basal diet and supplement was strategically developed to design balanced ration. This research aimed to obtain the proper concept of the agricultural by product usages based on the different rate of energy and protein sources of feed in related to increase the growth rate of beef cattle. The research was carried out into three studies. Study 1, to examine the nutritive value of basal diet and supplement, to determine in vitro and in sacco degradability and to determine the best combination of basal diet and supplement based on nutritive value and degradability. Results of Study 1 showed that crude protein of corn waste (8.7%) was higher than that of coffee pulps (6.6%)